Faktor Pendukung dan Penghambat Program Stop Buang Air Besar Sembarangan (BABS) di Wilayah Kerja Puskesmas Maronggela Kecamatan Riung Barat Kabupaten Ngada - Ruba, Yohanes Emanuel; Joko, Tri; Budiyono, Budiyono (Jurnal Riset Kesehatan Masyarakat, 2021)
Total sanitation is a condition when people do not open defecation. The impact of the Stop open defecation program is that it can trigger public awareness to change from poor sanitation conditions to better ones so that it can influence the community to improve sanitation conditions without assistance from the government. This study aims to determine the supporting and inhibiting factors of the Stop open defecation program in the working area of the Maronggela Health Center, Riung Barat District, Ngada Regency. Methods: The type of research used is observational research with a qualitative descriptive approach. The sampling technique was purposive sampling and conducted by interview. The number of samples in this study were 31 people consisting of sanitarians/facilitators, health workers, health cadres, community leaders, village officials, family heads and community members. This research was conducted in the working area of the Maronggela Health Center in April – May 2021. Results: The results showed that there were 8 supporting variables and 3 variables that did not support the implementation of the stop defecation program in the Maronggela Health Center work area. The supporting variables include resources, attitudes and beliefs, availability of facilities/facilities, the role of the head of the family, the role of health workers, the role of health cadres, the role of community leaders and the role of the village government, while the obstacles include knowledge, education level and economic status. Conclusion: Based on the results of the study, it can be concluded that the variables that support the implementation of the program are more than the variables that hinder it.